Laser cutting method and neodymium-iron-boron magnet prepared through laser cutting method

By debugging multiple parameters of laser cutting equipment and combining cutting nozzles and nitrogen blowing technology, the problems of slow speed and poor interface properties during the cutting process of neodymium iron boron magnets are solved, and efficient cutting and good magnet performance are achieved.

CN119387898APending Publication Date: 2025-02-07NINGBO KONIT IND +4
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411794284.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When cutting neodymium iron boron magnets, the processing speed is slow, the process is cumbersome, and the dimension requirements are difficult to guarantee. The cutting workpiece has problems such as poor cutting interface properties and poor mechanical properties.

Method used

Using laser cutting method, the laser energy parameters are controlled in the range of 15-60 by debugging the parameters of the frequency, duty cycle, peak power percentage, maximum peak power, speed and pulse width of the laser cutting equipment. Inside, ensure cutting quality.

Benefits of technology

The high-efficiency cutting of neodymium iron boron magnets is achieved. The prepared magnets have good cutting interface properties and mechanical properties, the width and depth of the phase change zone are suitable, and the surface roughness and bending strength are good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387898A_ABST
    Figure CN119387898A_ABST
Patent Text Reader

Abstract

The invention discloses a laser cutting method which can efficiently cut a neodymium-iron-boron magnet, and the prepared neodymium-iron-boron magnet has good cutting interface property and mechanical property. Specifically, the method comprises the following steps: S01, preparing a neodymium-iron-boron magnet for later use; s02, laser cutting equipment is debugged, and the frequency F, the duty ratio Q, the peak power percentage C, the maximum peak power P, the speed V and the pulse width B of laser are set; s03, mounting a cutting nozzle below the laser head; s04, cutting the neodymium iron boron magnet; in the step S02, the range of the maximum peak power P is 500-2000 w, the range of the duty ratio Q is 3%-50%, and the range of the peak power percentage C is 6%-100%; r is defined as a laser energy parameter to represent the energy output of the laser cutting equipment, and R is the product of the maximum peak power P, the duty ratio Q and the peak power percentage C, namely R = P * Q * C; and the range of the laser energy parameter R is 15-60.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to the technical field of laser processing. More specifically, the present disclosure relates to a laser cutting method and a NdFeB magnet product prepared therefrom. Background Art

[0002] Rare earth permanent magnet NdFeB material is known as the "king of magnets" for its high remanence, high coercivity, high magnetic energy product and good dynamic recovery characteristics. With the increasing demand for NdFeB magnetic materials, higher requirements are placed on its processing efficiency. At present, the most common processing method for NdFeB magnetic materials is traditional mechanical processing. However, for the processing of special-shaped magnets, the mechanical cutting method has a relatively slow processing speed, a long process, a cumbersome processing process, low efficiency, and difficulty in ensuring the size requirements, which has certain disadvantages.

[0003] The processing method of laser cutting is to use a high-power density laser beam to irradiate the substrate, so that the material is quickly heated to the vaporization temperature, evaporated to form holes, and as the beam moves on the material, the holes continuously form a very narrow slit to complete the cutting of the material, especially in cutting special-shaped products. This method has high processing efficiency, high flexibility, high yield rate and can be intelligent, with great development potential. Chinese patent application CN115781052A discloses a laser cutting technology that uses quasi-continuous fiber laser to cut neodymium iron boron magnets. It can avoid the problem of overburning caused by long dwell time of continuous mode laser cutting, but the workpiece after cutting has poor cutting interface properties and poor mechanical properties.

[0004] In view of this, there is an urgent need to provide a laser cutting method that can efficiently cut NdFeB magnets, and the prepared NdFeB magnets have good cutting interface properties and mechanical properties. Summary of the invention

[0005] In order to at least solve one or more of the technical problems mentioned above, the present disclosure proposes a laser cutting method and a NdFeB magnet product prepared therefrom in multiple aspects.

[0006] In a first aspect, the present application provides a laser cutting method, characterized in that it comprises the following steps:

[0007] S01. Prepare NdFeB magnets for use;

[0008] S02. Debug the laser cutting equipment and set the laser frequency F, duty cycle Q, peak power percentage C, maximum peak power P, speed V, and pulse width B;

[0009] S03. Install the cutting nozzle under the laser head;

[0010] S04. Cutting the NdFeB magnet;

[0011] In the step S02, the range of the maximum peak power P satisfies 500-2000w, the range of the duty cycle Q satisfies 3%-50%, and the range of the peak power percentage C satisfies 6%-100%;

[0012] Define R as a laser energy parameter to represent the energy output of the laser cutting equipment. R is the product of the maximum peak power P, the duty cycle Q and the peak power percentage C, that is:

[0013] R = P*Q*C;

[0014] The laser energy parameter R is within the range of 15-60.

[0015] According to one embodiment of the present application, in step S02, the laser of the laser cutting device satisfies at least one of the following conditions:

[0016] a. The frequency F range meets 0-1.2kHz;

[0017] b. The speed V range is 0.5-4m / min;

[0018] c. The pulse width B ranges from 0.05 to 50 ms.

[0019] According to one embodiment of the present application, in the step S02, the focal position of the laser of the laser cutting device is also set, and the focal position is -1-+1 mm; preferably, the focal position is 0.7-0.9 mm.

[0020] According to one embodiment of the present application, in step S03, the diameter of the gas guide hole of the cutting nozzle is 1.0-1.5 mm, and the derived gas is an inert gas.

[0021] According to one embodiment of the present application, in step S02, the laser of the laser cutting device satisfies at least one of the following conditions:

[0022] a. The duty cycle Q ranges from 10% to 30%;

[0023] b. The peak power percentage C ranges from 7% to 50%;

[0024] c. The laser energy parameter R is within the range of 20-35.

[0025] According to one embodiment of the present application, in step S04, when the NdFeB magnet is cut, nitrogen is blown into the cutting portion; preferably, the pressure of the blown nitrogen is 0.2-1 MPa.

[0026] In a second aspect, the present disclosure provides a NdFeB magnet product, wherein the composition of the NdFeB magnet is RTBM;

[0027] Wherein, R is a rare earth element, and the content of R is 28-30.5wt%; the content of B element is 0.85-1.05wt%;

[0028] M includes any one of Cu, Ga, Zr, Ti, Nb, Al, Ag, W, and Mn, or a combination of at least two thereof; the content of M is 0 to 3 wt% and does not include 0;

[0029] T includes Fe and / or Co, and the content of T is the remainder after removing R, B and M;

[0030] The NdFeB magnet comprises a phase change region, and the width of the phase change region is 2 μm-15 μm.

[0031] According to one embodiment of the present application, the depth of the phase change zone is 20 μm-30 μm.

[0032] According to one embodiment of the present application, the NdFeB magnet has a magnet surface formed by laser cutting, and the roughness Ra of the magnet surface satisfies the range of 0.8 μm-3 μm.

[0033] According to one embodiment of the present application, the NdFeB magnet has a high temperature demagnetization rate of 3.0%-6.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] By reading the following detailed description with reference to the accompanying drawings, the above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein:

[0035] Figure 1 A flow chart of a laser cutting method according to an embodiment of the present disclosure is shown;

[0036] Figure 2 An electron microscope image of a magnet cross section perpendicular to the laser cutting direction of a magnet 1 sample prepared according to Example 1 of the present disclosure is shown.

[0037] Figure 3 An electron microscope image of a magnet cross section perpendicular to the laser cutting direction of a magnet 3 sample prepared according to comparative example 1 of the present disclosure is shown.

[0038] Figure 4 The electron microscope image of the magnet cross section perpendicular to the laser cutting direction and the related energy spectrum analysis are shown. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present disclosure to clearly and completely describe the technical solutions in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0040] It should be understood that the terms "include" and "comprising" used in the specification and claims of the present disclosure indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or collections thereof.

[0041] It should also be understood that the terms used in this disclosure are only for the purpose of describing specific embodiments and are not intended to limit the disclosure. As used in this disclosure and claims, the singular forms of "a", "an", and "the" are intended to include the plural forms unless the context clearly indicates otherwise. It should also be further understood that the term "and / or" used in this disclosure and claims refers to any combination of one or more of the associated listed items and all possible combinations, including these combinations.

[0042] The specific implementation of the present disclosure is described in detail below with reference to the accompanying drawings.

[0043] Figure 1 FIG. 1 shows a flow chart of a laser cutting method according to an embodiment of the present disclosure. Figure 1 As shown in, in the first aspect, the present application provides a method for laser cutting, comprising the following steps: S01. Prepare NdFeB magnets for use; S02. Debug the laser cutting equipment, set the laser frequency F, duty cycle Q, peak power percentage C, maximum peak power P, speed V, and pulse width B; S03. Install a cutting nozzle under the laser head; S04. Cut the NdFeB magnets.

[0044] In the step S02, the maximum peak power P is within a range of 500-2000w, the duty cycle Q is within a range of 3%-50%, and the peak power percentage C is within a range of 6%-100%.

[0045] Define R as a laser energy parameter to represent the energy output of the laser cutting equipment. R is the product of the maximum peak power P, the duty cycle Q and the peak power percentage C, that is, R=P*Q*C; the range of the laser energy parameter R satisfies 15-60.

[0046] In laser processing technology (especially laser cutting technology), the most critical factor is the processing energy, which is closely related to factors such as maximum peak power, duty cycle, and peak power percentage. Among them, the duty cycle refers to the ratio of the working time of the laser pulse to the total cycle time, reflecting the time period ratio of the laser pulse operation. The maximum peak power of the laser refers to the maximum power value instantly reached by the laser during the output pulse process; it is usually used to describe the power characteristics of the laser output pulse and is one of the important indicators for measuring laser performance. The peak power percentage refers to the ratio of the average power to the maximum peak power.

[0047] It can be seen that R can be defined as a laser energy parameter to represent the processing energy output of the laser cutting equipment. R is the product of the maximum peak power P, the duty cycle Q and the peak power percentage C, that is, R = P*Q*C. When the range of the laser energy parameter R meets 15-60, the energy output of the laser cutting equipment can effectively cut the NdFeB magnets without overburning or seriously affecting the properties and mechanical properties of the NdFeB magnet cutting interface. When the laser energy parameter R<15, the duty cycle Q or the peak power percentage C is insufficient, and the NdFeB magnet cannot be effectively cut. It may also cause problems such as poor cutting quality or poor roughness of the cutting interface. When the laser energy parameter R>60, the duty cycle Q or the peak power percentage C is too large, the laser equipment may overheat, the properties of the NdFeB magnet cutting interface may deteriorate, and even shorten the life of the laser or damage it.

[0048] In some embodiments, the laser of the laser cutting equipment has a frequency F in the range of 0-1.2kHz. Exemplarily, the frequency F can be 1.2kHz, 1.0kHz, 0.8kHz, 0.6kHz, 0.4kHz, 0.2kHz or any value within the range formed by any of the above numerical values. The laser frequency affects the laser processing speed and the accumulation of heat. The higher the frequency, the more pulses act on the material per unit time, the faster the processing speed, but the more heat is accumulated. Selecting a suitable laser frequency is conducive to efficiently cutting NdFeB magnets, and will not seriously affect the properties of the NdFeB magnet cutting interface.

[0049] In some embodiments, the laser of the laser cutting device has a processing speed V in the range of 0.5-4m / min. For example, the processing speed V can be 4m / min, 3.5m / min, 3m / min, 2.5m / min, 2m / min, 1.5m / min, 1m / min, 0.5m / min or any value in the range of any of the above values. In some embodiments, the laser of the laser cutting device has a pulse width B in the range of 0.05-50ms. For example, the pulse width B can be 50ms, 45ms, 40ms, 35ms, 30ms, 25ms, 20ms, 15ms, 10ms, 5ms, 2.5ms, 1ms, 0.05ms or any value in the range of any of the above values. There is a certain relationship between laser processing speed and pulse width; pulse width refers to the duration of the laser pulse, and a shorter pulse width can provide a higher energy density, which helps to improve the laser processing speed and processing quality. In the laser cutting process, pulse width also affects cutting quality and efficiency. Shorter pulse widths provide higher energy density for applications requiring fine cutting, while longer pulse widths are suitable for applications requiring greater cutting depth.

[0050] In some embodiments, in step S02, the focal position of the laser of the laser cutting device is also set, and the focal position is -1-+1mm; preferably, the focal position is 0.7-0.9mm. The focal position refers to the position of the point formed after the laser beam is focused, which affects the energy density distribution of the laser.

[0051] In some embodiments, in step S03, the diameter of the air guide hole of the cutting nozzle is 1.0-1.5 mm, and the derived gas is an inert gas. Exemplarily, the diameter of the air guide hole of the cutting nozzle can be 1.5 mm, 1.4 mm, 1.3 mm, 1.2 mm, 1.1 mm, 1.0 mm, or any value within the range of any of the above values. The derived inert gas can protect the laser head, remove molten material, cool the processing area, etc. during the laser cutting process.

[0052] In some embodiments, in step S04, when cutting the NdFeB magnet, the cutting nozzle will blow nitrogen into the cutting part. In some embodiments, the pressure of the nitrogen blown in is 0.2-1MPa. Exemplarily, the pressure of the nitrogen blown in can be 1MPa, 0.8MPa, 0.6MPa, 0.4MPa, 0.2MPa or any value within the range composed of any of the above numerical values. Since nitrogen can protect the laser head and cool the processing area during laser cutting, it is particularly important to control the pressure of the nitrogen blown in to a suitable range such as 0.2-1MPa when cutting the NdFeB magnet; if the pressure of the nitrogen blown in is too small (e.g. <0.2MPa), it cannot fully cool the processing area; if the pressure of the nitrogen blown in is too large (e.g. >1MPa), the sample may be blown away, causing the cutting process to be interrupted.

[0053] In some embodiments, in step S02, the laser of the laser cutting device meets the following conditions: the duty cycle Q ranges from 10% to 30%. For example, the duty cycle Q can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30% or any value within the range of any of the above values.

[0054] In some embodiments, in step S02, the laser of the laser cutting device meets the following conditions: the peak power percentage C is in the range of 7%-50%. For example, the peak power percentage C can be 7%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any value within the range of any of the above values.

[0055] In some embodiments, in step S02, the laser of the laser cutting device meets the following conditions: the laser energy parameter R is in the range of 20-35. Exemplarily, the laser energy parameter R can be 20, 22, 24, 26, 28, 30, 32, 34 or any value within the range of any of the above values.

[0056] In the second aspect, the present application also provides a NdFeB magnet, the composition of which is RTBM; wherein R is a rare earth element, and the content of R is 28-30.5wt%; the content of B element is 0.85-1.05wt%; M includes any one of Cu, Ga, Zr, Ti, Nb, Al, Ag, W, and Mn, or a combination of at least two; the content of M is 0-3wt% and does not include 0; T includes Fe and / or Co, and the content of T is the remainder of R, B and M; the NdFeB magnet includes a phase change region. In some embodiments, the NdFeB magnet has a phase change region with a width of 2μm-15μm. Exemplarily, the width of the phase change region can be 2μm, 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, or any value within the range composed of any of the above values.

[0057] In some embodiments, the NdFeB magnet has a phase change region with a depth of 20 μm-30 μm. For example, the depth of the phase change region can be 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, or any value within the range of any of the above values.

[0058] The present application controls various parameters of the laser cutting process so that the NdFeB magnet after cutting has a phase change zone with a smaller width and a shallower depth, indicating that the laser energy causes less damage to the NdFeB magnet and the damaged layer of the NdFeB magnet is shallow, thereby making the NdFeB magnet after laser cutting have better magnetic properties, surface roughness and bending strength.

[0059] In some embodiments, the NdFeB magnet has a magnet surface formed by laser cutting, and the roughness Ra of the magnet surface satisfies the range of 0.8 μm-3 μm. Exemplarily, the roughness Ra of the magnet surface can be 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3.0 μm or any value within the range formed by any of the above values.

[0060] In some embodiments, the NdFeB magnet has a high temperature demagnetization rate of 3.0%-6.5% (preferably 4.0%-5.2%). Exemplarily, the high temperature demagnetization rate of the NdFeB magnet can be 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5% or any value within the range of any of the above values.

[0061] Example

[0062] In order to make it easier to understand the laser cutting method of the disclosed embodiment, it will be described below with reference to specific examples.

[0063] The test methods used in this application are as follows:

[0064] Width and depth of phase change zone: Microstructure observation was performed on the magnet surface perpendicular to the laser cutting direction, such as Figure 4 As shown in the left figure, Figure 4 The bottom of the left picture shows the surface of the magnet cut by laser. EDS energy dispersive X-ray spectroscopy line scanning analysis is performed from the magnet surface to the inside of the magnet at the center of the magnet surface to measure the distribution of Fe, Pr, Nd, Dy, and Tb element contents. The EDS energy spectrum analysis results are shown in Figure 1. Figure 4 As shown in the right figure, it is found that Fe, Pr, Nd, Dy, and Tb all have an X-ray diffraction peak drastic change at the same position. The diffraction peak of Fe element appears as a trough, the diffraction peaks of Pr and Nd elements appear as peaks, and the diffraction peaks of Dy and Tb elements appear as troughs. Among them, the trough of the diffraction peak of Fe is more significant. In the microstructure diagram, the position of the diffraction peak drastic change shows a black particle aggregation area. After research, it was found that the black particles are α-Fe.

[0065] The inventors analyzed the reasons for the sudden change in the contents of Fe, Pr, Nd, Dy and Tb elements and believed that the high temperature during laser cutting caused the main phase to re-melt and precipitate α-Fe. At the same time, the rare earths Pr and Nd with lower melting points became liquid phases to wrap α-Fe, forming a phase change zone, which is specifically marked as follows: Figure 4 In this application, the trough width of the Fe element diffraction peak is defined as the width of the phase change zone, which is specifically indicated as follows: Figure 4 As shown in W, the distance between the x-axis position of the trough vertex of the Fe element diffraction peak and the magnet surface position is defined as the depth of the phase change region, which is specifically marked as follows Figure 4 As shown in D. In some embodiments, the diffraction peak of the Fe element may have two or more drastic changes, that is, two troughs or multiple troughs may appear, and correspondingly, the diffraction peaks of the Pr and Nd elements may have two or more peaks. The width of the phase change zone is calculated according to the distance between the starting end position of the first trough of the diffraction peak of the Fe element and the ending end of the last trough, and the depth of the phase change zone is calculated according to the maximum value of the distance between the x-axis position corresponding to each trough vertex and the surface position of the magnet. It should be noted that the test should be conducted 10 times at different positions in the central area of ​​the same sample, and the maximum value of the 10 times is taken as the width and depth of the phase change zone. The smaller the width value of the phase change zone, the less damage the laser energy causes to the magnet, the smaller the depth of the phase change zone, and the shallower the damaged layer of the magnet.

[0066] Roughness test method for cutting surface: Use a roughness tester to test the roughness distribution of the surface of the NdFeB magnet. For each sample, use the stylus of the roughness tester to gently slide along the cutting surface, record the changes in the surface profile, and count the data of 10 NdFeB magnets and calculate the average value, which is recorded as Ra.

[0067] Bending strength test method: Using the three-point bending test method, the sample is placed on two supporting points and a loading point is applied in the middle. The force applied by the loading point bends the sample until the sample breaks. The bending strength is calculated by measuring the applied force and the geometric dimensions of the sample.

[0068] High-temperature demagnetization rate of the magnet: After the magnet is saturated and magnetized, use M-axis to measure the magnetic moment value 1 of the magnet, then put the magnet on an aluminum plate and put it in an oven, heat it to 150℃ and keep it warm for 2h, measure the magnetic moment value 2 of the magnet after cooling to room temperature, and calculate the high-temperature demagnetization rate = (magnetic moment value 1-magnetic moment value 2) / magnetic moment value 1*100%.

[0069] The specific preparation steps of the NdFeB magnet substrate in the following examples and comparative examples are as follows:

[0070] In the smelting process, R-T-B-M alloy powder is prepared according to the mass percentage wt%, wherein R is Pr, Nd and Dy, M includes Cu, Ga, Al and Ti, and T includes Fe and Co; wherein PrNd is 30wt%, Dy is 0.6wt%, Ga is 0.1wt%, Cu is 0.15wt%, Co is 1.1wt%, Al is 0.3wt%, Ti is 0.14wt%, B is 0.92wt%, and the balance is Fe. The prepared raw materials are put into a vacuum induction melting furnace, heated to 1350°C, fully melted into alloy steel liquid, poured onto a quenching roller and rapidly cooled to form an alloy sheet, and a 0.25mm thick alloy sheet is obtained after secondary cooling.

[0071] In the powder making process, the obtained alloy sheet is subjected to hydrogen embrittlement treatment and air flow mill grinding to obtain air flow milled powder with an average particle size SMD of 3.0 μm.

[0072] In the molding process, 0.2 wt% of lubricant is added to the air flow mill, and the mixture is mixed by a mixer for 120 minutes until the mixture is evenly dispersed. The mixture is pressed under nitrogen protection and an external 2T magnetic field, and a green body is obtained after cold isostatic pressing.

[0073] In the sintering process, the green body is placed in a vacuum sintering furnace, kept at 1045℃ for 300min, cooled to room temperature; then kept at 1080℃ for 300min, cooled to room temperature. The green body after sintering is further subjected to the first aging treatment at 900℃ for 240min, and the second aging treatment at 530℃ for 360min, and then cooled out of the furnace to obtain the NdFeB magnet blank.

[0074] Machining process: the NdFeB magnet blank is machined into a 60*45*0.4mm thin sheet (ie, the thickness is 0.4mm) to obtain the magnet I to be laser cut. Alternatively, the NdFeB magnet blank is machined into a 60*45*1.5mm thin sheet (ie, the thickness is 1.5mm) to obtain the magnet II to be laser cut.

[0075] Example 1 (Laser cutting process L of the present application for cutting magnet I with a thickness of 0.4 mm)

[0076] The process parameters of the laser cutting process L are as follows: the frequency setting range of the laser is 1kHz; the speed setting range is 3.5m / min, and the focal position is 0.9mm; the diameter of the air guide hole of the cutting nozzle is 1mm, and the gas discharged is nitrogen. During cutting, nitrogen will be blown into the cutting part, and the nitrogen pressure is 0.8MPa.

[0077] In addition, the maximum peak power P is 2000W, the duty cycle Q is 14%, and the peak power percentage C is 10%. Laser energy parameter R in laser cutting process L L It is the product of the maximum peak power P, the duty cycle Q and the peak power percentage C, that is: R L is 28.

[0078] The implementation steps of laser cutting process L for cutting magnet I are as follows: prepare NdFeB magnet sample magnet I for use; debug the laser cutting equipment according to the process parameters of the above-mentioned laser cutting process L, set the laser frequency F, duty cycle Q, peak power percentage C, maximum peak power P, speed V, and also set the laser focus position and other parameters; install a cutting nozzle under the laser head, and set the cutting nozzle according to the process parameters of the above-mentioned laser cutting process; cut the NdFeB magnet sample magnet I to obtain magnet 1.

[0079] like Figure 2 As shown, according to the electron microscope photos and EDS energy spectrum line scanning results, after being cut by the laser cutting process, the phase change zone width of the magnet 1 is measured to be about 7μm, and the phase change zone depth is about 25μm.

[0080] The roughness of the magnet surface formed by laser cutting was measured to be 1.20 μm, and the bending strength of the sample was measured to be 0.32 MPa.

[0081] The average value of the high temperature demagnetization rate of the 10 magnets 1 was measured to be 5.2%.

[0082] Example 2 (Laser cutting process L of the present application for cutting magnet II with a thickness of 1.5 mm)

[0083] The process parameters of laser cutting process L are as follows: laser cutting of NdFeB workpieces, the frequency setting range of the laser is 1.2kHz; the speed setting range is 3mm / s, and the focus position is 0.7mm; the diameter of the air guide hole of the cutting nozzle is 1.5mm, and the gas discharged is nitrogen. During cutting, nitrogen will be blown into the cutting part, and the nitrogen pressure is 0.4MPa.

[0084] In addition, the maximum peak power P is 1500W, the duty cycle Q is 40%, and the peak power percentage C is 10%. Laser energy parameter R in laser cutting process L L It is the product of the maximum peak power P, the duty cycle Q and the peak power percentage C, that is: R L is 60.

[0085] The implementation steps of laser cutting process L for cutting magnet II are as follows: prepare NdFeB sample magnet II for use; debug the laser cutting equipment according to the process parameters of the above-mentioned laser cutting process L, set the laser frequency F, duty cycle Q, peak power percentage C, maximum peak power P, speed V, and also set the laser focus position and other parameters; install a cutting nozzle under the laser head, and set the cutting nozzle according to the process parameters of the above-mentioned laser cutting process; cut the NdFeB sample magnet II, and the magnet obtained after cutting is magnet 2.

[0086] According to the electron microscope photos and EDS energy spectrum line scanning results, the width of the phase change zone of magnet 2 is about 10μm and the depth is about 30μm.

[0087] The roughness of the magnet surface formed by laser cutting was measured to be 2.5 μm, and the bending strength of the sample was measured to be 5.1 MPa.

[0088] The average value of the high-temperature demagnetization rate of the ten magnets 2 was measured to be 4.5%.

[0089] Comparative Example 1 (Comparative Laser Cutting Process H Cutting Magnet I with a Thickness of 0.4 mm)

[0090] The process parameters of laser cutting process H are as follows: laser cutting of NdFeB workpieces, the frequency setting range of the laser is 1.2kHz; the speed setting range is 3.5m / min, and the focus position is 0.9mm; the diameter of the air guide hole of the cutting nozzle is 1mm, and the gas discharged is nitrogen. During cutting, nitrogen will be blown into the cutting part, and the nitrogen pressure is 0.8MPa.

[0091] And, the maximum peak power P is 1500W, the duty cycle Q is 9%, and the peak power percentage C is 10%. Laser energy parameter R in laser cutting process H H It is the product of the maximum peak power P, the duty cycle Q and the peak power percentage C, that is: RH It is 13.5.

[0092] The implementation steps of cutting magnet I by laser cutting process H are as follows: prepare NdFeB sample magnet I for standby; debug laser cutting equipment according to the process parameters of the above laser cutting process H, set the laser frequency F, duty cycle Q, peak power percentage C, maximum peak power P, speed V, and also set the laser focus position and other parameters; install a cutting nozzle under the laser head, and set the cutting nozzle according to the process parameters of the above laser cutting process; cut NdFeB sample magnet I. The magnet 3 obtained after cutting.

[0093] like Figure 3 As shown, based on the electron microscope photos and EDS energy spectrum line scanning results, it was measured that the width of the phase change zone of magnet 3 is about 17μm and the depth is about 35μm.

[0094] The roughness of the magnet surface formed by laser cutting was measured to be 3.5 μm, and the bending strength of the sample was measured to be 0.27 MPa.

[0095] The average value of the high-temperature demagnetization rates of the ten magnets 3 was measured to be 7.6%.

[0096] Comparative Example 2 (Comparative Laser Cutting Process H Cutting Magnet II with a Thickness of 1.5 mm)

[0097] The process parameters of laser cutting process H are as follows: laser cutting of NdFeB workpieces, the frequency setting range of the laser is 1.2kHz; the speed setting range is 3mm / s, and the focus position is 0.7mm; the diameter of the air guide hole of the cutting nozzle is 1.5mm, and the gas discharged is nitrogen. During cutting, nitrogen will be blown into the cutting part, and the nitrogen pressure is 0.4MPa.

[0098] And, the maximum peak power P is 1500W, the duty cycle Q is 15%, and the peak power percentage C is 40%. Laser energy parameter R in laser cutting process H H It is the product of the maximum peak power P, the duty cycle Q and the peak power percentage C, that is: R H is 90.

[0099] The implementation steps of laser cutting process H for cutting magnet II are as follows: prepare NdFeB sample magnet II for standby; debug laser cutting equipment according to the process parameters of the above laser cutting process H, set the laser frequency F, duty cycle Q, peak power percentage C, maximum peak power P, speed V, and also set the laser focus position and other parameters; install a cutting nozzle under the laser head, and set the cutting nozzle according to the process parameters of the above laser cutting process H; cut NdFeB magnet II. The magnet obtained after cutting is magnet 4.

[0100] According to the electron microscope photos and energy spectrum results, it was measured that the width of the phase change zone of magnet 4 is about 30μm and the depth is about 48μm.

[0101] The roughness of the magnet surface formed by laser cutting was measured to be 3.8 μm, and the bending strength of the sample was measured to be 4.6 MPa.

[0102] The average value of the high-temperature demagnetization rates of the ten magnets 4 was measured to be 8.4%.

[0103] From the situation of Example 1 and Comparative Example 1, Example 1 has a phase change zone with a smaller width and depth, a lower high-temperature demagnetization rate, a higher bending strength value, and a smaller surface roughness. From the situation of Example 2 and Comparative Example 2, Example 2 has a phase change zone with a smaller width and depth, a lower high-temperature demagnetization rate, a higher bending strength value, and a smaller surface roughness. It can be seen that by controlling the laser processing technology, the width and depth of the phase change zone can be reduced, so that the component segregation in the phase change zone has less effect on the magnet, thereby improving the magnetic properties, surface roughness and bending strength of the magnet.

[0104] Although multiple embodiments of the present disclosure have been shown and described herein, it will be apparent to those skilled in the art that such embodiments are provided by way of example only. Those skilled in the art may think of many changes, modifications, and alternatives without departing from the thought and spirit of the present disclosure. It should be understood that in the process of practicing the present disclosure, various alternatives to the embodiments of the present disclosure described herein may be adopted. The attached claims are intended to define the scope of protection of the present disclosure, and therefore cover equivalents or alternatives within the scope of these claims.

Claims

1. A laser cutting method, characterized in that: The following steps are involved: S01. Prepare NdFeB magnets for use; S02. Debug the laser cutting equipment and set the laser frequency F, duty cycle Q, peak power percentage C, maximum peak power P, speed V, and pulse width B; S03. Install the cutting nozzle under the laser head; S04. Cutting the NdFeB magnet; In the step S02, the range of the maximum peak power P satisfies 500-2000w, the range of the duty cycle Q satisfies 3%-50%, and the range of the peak power percentage C satisfies 6%-100%; Define R as a laser energy parameter to represent the energy output of the laser cutting equipment. R is the product of the maximum peak power P, the duty cycle Q and the peak power percentage C, that is: R = P*Q*C; The laser energy parameter R is within the range of 15-60.

2. The method according to claim 1, characterized in that In step S02, the laser of the laser cutting device satisfies at least one of the following conditions: a. The frequency F range meets 0-1.2kHz; b. The speed V range is 0.5-4m / min; c. The pulse width B ranges from 0.05 to 50 ms.

3. The method according to claim 1 or 2, characterized in that: In the step S02, the focal position of the laser of the laser cutting device is also set, and the focal position is -1-+1 mm; preferably, the focal position is 0.7-0.9 mm.

4. The method according to claim 1 or 2, characterized in that: In the step S03, the diameter of the gas guide hole of the cutting nozzle is 1.0-1.5 mm, and the derived gas is an inert gas.

5. The method according to claim 1 or 2, characterized in that: In step S02, the laser of the laser cutting device satisfies at least one of the following conditions: a. The duty cycle Q ranges from 10% to 30%; b. The peak power percentage C ranges from 7% to 50%; c. The laser energy parameter R is within the range of 20-35.

6. The method according to claim 1 or 2, characterized in that: In the step S04, when cutting the NdFeB magnet, the cutting nozzle will blow nitrogen into the cutting part; preferably, the pressure of the blown nitrogen is 0.2-1 MPa.

7. A NdFeB magnet, wherein the composition of the NdFeB magnet is RTBM; in, R is a rare earth element, and the content of R is 28-30.5wt%; the content of B element is 0.85-1.05wt%; M includes any one of Cu, Ga, Zr, Ti, Nb, Al, Ag, W, and Mn, or a combination of at least two thereof; the content of M is 0 to 3 wt% and does not include 0; T includes Fe and / or Co, and the content of T is the remainder after removing R, B and M; The NdFeB magnet comprises a phase change region, and the width of the phase change region is 2 μm-15 μm. 8 . The NdFeB magnet according to claim 7 , wherein the depth of the phase change region is 20 μm-30 μm. 9 . The NdFeB magnet according to claim 7 , wherein the NdFeB magnet has a magnet surface formed by laser cutting, and the roughness Ra of the magnet surface satisfies the range of 0.8 μm-3 μm. 10 . The NdFeB magnet according to claim 7 , having a high temperature demagnetization rate of 3.0% to 6.5%.

Citation Information

Patent Citations

  • Method for cutting neodymium iron boron through quasi-continuous QCW optical fiber laser

    CN115781052A